Cycle time minimization in production line using robust hybrid optimization algorithm - Noorazliza, Sulaiman (2021)
Bio-inspired algorithms that have been introduced by mimicking the biological phenomenon of nature have widely implemented to cater various real-world problems. As example, memetic algorithm, EGSJAABC3 is applied for economic environmental dispatch (EED) optimization, Hybrid Pareto Grey Wolf Optimization to minimize emission of noise and carbon in U-shaped robotic assembly line and Polar Bear Optimization to optimize heat production. The results obtained from their research have clearly portrayed the robustness of bio-inspired algorithms to cater complex problems. Assembly line, which is normally the last step of production that involves final assembly of the products. An assembly line generally consists of several workstations placed in sequential order. Each of the workstation is in charge to complete certain specific jobs. Hence, it is a must to make the best use of the efficiency of the assembly line. Cycle time minimization is part of the assembly line balancing problem due to its uncertainty that dependent on the number of manpower, material preparation and machine capacity. Cycle time basically means time needed to process a product using a specific task in a production line. This project proposes the application of new hybrid optimization algorithm named JAABC5-RRO to minimize cycle time to produce a new audio product on a production line in a production company.